Multidisciplinary approaches to crowdfunding platforms - Negrão, Carla Sofia Vicente, 1978-; Brito, João António Furtado, 1978- (Advances in e-business research series., 2021)
""This book examines the current state of crowdfunding. It also explores challenges, opportunities, and limitations of crowdfunding"--Provided by publisher"--